1999
DOI: 10.1023/a:1008301314812
|View full text |Cite
|
Sign up to set email alerts
|

The influence of familial and hereditary factors on the prognosis of breast cancer

Abstract: Conflicting data exist as to whether the prognosis of familial or hereditary breast cancer differs from that of sporadic cases. Some of the discrepancies may be explained by methodological differences or biases. However, no studies showed a survival advantage for BRCA1 mutation carriers. This seems to indicate that BRCA1-related breast cancer is not associated with a survival advantage, and that in fact, certain BRCA1 germline mutations confer a worse prognosis. However, to adequately answer this question, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 49 publications
1
40
0
1
Order By: Relevance
“…This yielded five reviews (58)(59)(60)(61)(62). None of the reviews included pooled analyses of study outcomes, and thus, the included original articles were retrieved and examined.…”
Section: A2 Literature Searches Regarding Input Values For the Modelmentioning
confidence: 99%
“…This yielded five reviews (58)(59)(60)(61)(62). None of the reviews included pooled analyses of study outcomes, and thus, the included original articles were retrieved and examined.…”
Section: A2 Literature Searches Regarding Input Values For the Modelmentioning
confidence: 99%
“…Therefore, a large proportion of the familial clustering of breast and ovarian cancer remains unexplained. Particular clinicopathological characteristics and differences in outcome have been reported for cases of breast cancer developing in familial clusters compared to sporadic cases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting data exist on the impact of a family history of breast or ovarian cancer on the outcome of breast cancer (Ruder et al, 1988;Chappuis et al, 1999;Russo et al, 2002). Some studies have shown improved survival rates among breast cancer patients with affected relatives compared to those without a family history (Malone et al, 1996;Mohammed et al, 1998), some reported poorer survival rates (Slattery et al, 1993;Gonzalez-Angulo et al, 2005), and others did not find any survival difference between patients with or without a family history (Greenberg et al, 1985;Kinoshita et al, 2004).…”
mentioning
confidence: 99%